2011
DOI: 10.4103/0974-7796.82170
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized trial of 100u vs 200u botox in the treatment of idiopathic overactive bladder

Abstract: Aim:To evaluate the clinical outcomes of two different doses of BTX-A in patients with refractory idiopathic overactive bladder.Patients and Methods:Thirty nine patients with refractory idiopathic overactive bladder from 1/1/2008 till 30/3/2009 were evaluated in a tertiary care hospital. Patients were evaluated using urodynamic studies, voiding diary, UDI-6 and IIQ-7 questionnaires prior to being prospectively randomized (alternate randomization) to the BTX-A applications and three months after treatment. Void… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 10 publications
0
22
0
2
Order By: Relevance
“…In Denys et al's study [11], quality of life improvements were maintained for up to 6 months and generally lasted longer than clinical and urodynamic improvements. Quality of life was significantly improved in Altaweel et al's study [21] in both groups, with no statistically significant difference between 100 and 200 U at month 3. There were also no differences noted in Cohen et al's study [22] between those receiving 100 and 150 U botulinum toxin-A regarding improvement in quality of life (p > 0.05) at week 12.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In Denys et al's study [11], quality of life improvements were maintained for up to 6 months and generally lasted longer than clinical and urodynamic improvements. Quality of life was significantly improved in Altaweel et al's study [21] in both groups, with no statistically significant difference between 100 and 200 U at month 3. There were also no differences noted in Cohen et al's study [22] between those receiving 100 and 150 U botulinum toxin-A regarding improvement in quality of life (p > 0.05) at week 12.…”
Section: Resultsmentioning
confidence: 99%
“…No statistically significant difference was seen in Cohen et al's study [22] in the reduction of daily voiding frequency between patients receiving 100 U (p > 0.05) and 150 U (p > 0.05) botulinum toxin-A at week 12. Altaweel et al [21] found no statistically significant difference in voiding diary between 100 and 200 U (p > 0.05) at any time point.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations